Concept Analysis of Sexual Health in Patients with Gynecological Cancer - Atun Raudotul Ma'rifah; Yati Afiyanti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Gynecological cancer causes severe problems in a woman's life because it attacks the reproductive organs, which are very important and related to sexual health problems. Sexual health is an often-overlooked need when it comes to treating cancer patients. This article aims to explain the concept of sexual health or sexual well-being in patients with gynecologic cancer. The method used is the Walker and Avant concept approach. To advance knowledge, concept analysis will aid in refining and clarifying sexual health. The Walker and Avant Framework clarifies current sexual health understanding and use in practice and research across multiple disciplines. This concept's critical attributes include a person's ability to perform sexual functions, sexual satisfaction, self-esteem, and self-efficacy. The conclusion of this analysis concept is to increase nurses' knowledge about sexual health in patients with gynecological cancer to improve the patient quality of life. Abstrak: Kanker ginekologi menyebabkan masalah serius bagi kehidupan seorang wanita karena menyerang organ reproduksi yang merupakan bagian yang sangat penting yang erat kaitannya dengan masalah kesehatan seksual. Kesehatan seksual adalah kebutuhan yang sering diabaikan ketika datang ke perawatan pasien kanker. Tujuan dari artikel ini adalah untuk menjelaskan konsep kesehatan seksual atau kesejahteraan seksual pada pasien dengan kanker ginekologi. Metode yang digunakan adalah pendekatan konsep Walker dan Avant. Analisis konsep akan memungkinkan penyempurnaan dan klarifikasi kesehatan seksual untuk memajukan pengetahuan. Kerangka kerja Walker dan Avant digunakan untuk mengklarifikasi pemahaman saat ini dan penggunaan kesehatan seksual dalam praktik dan penelitian di berbagai disiplin ilmu. Atribut kritis dari konsep ini termasuk kemampuan seseorang untuk melakukan fungsi seksual, kepuasan seksual, harga diri, dan efikasi diri pada pasien dengan kanker ginekologi. Kesimpulan dari konsep analisis ini adalah untuk meningkatkan pengetahuan perawat tentang kesehatan seksual pada pasien dengan kanker ginekologi sehingga meningkatkan kualitas hidup pasien.